2003
DOI: 10.1046/j.1523-1755.2003.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β, TNF-α, TGF-β, and bFGF expression in bone biopsies before and after parathyroidectomy

Abstract: Based on these results, we suggest that IL-1beta, TNF-alpha, TGF-beta, and bFGF are involved in bone remodeling regulation, acting as local effectors, possibly under the control of PTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Bone marrow inflammatory cytokines are increased in patients with renal osteodystrophy 156,157 —a condition that is associated with erythropoietin resistance. A link between inflammation and decreased erythropoiesis was demonstrated by relatively decreased levels of serum erythropoietin in anaemic patients without renal failure who had inflammation caused by autoimmune disease 158 or malignancies 159 as opposed to levels in similarly anaemic patients without inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow inflammatory cytokines are increased in patients with renal osteodystrophy 156,157 —a condition that is associated with erythropoietin resistance. A link between inflammation and decreased erythropoiesis was demonstrated by relatively decreased levels of serum erythropoietin in anaemic patients without renal failure who had inflammation caused by autoimmune disease 158 or malignancies 159 as opposed to levels in similarly anaemic patients without inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroid hyperplasia and vitamin D deficiency are the major factors that play a critical role in the pathogenesis and pathophysiology [1]. However, recent studies have showed that in addition to parathyroid hormone (PTH), a multitude of local factors such as interleukins, growth factors and cytokines, are involved in the process of renal osteodystrophy [2,3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…Using immunohistochemistry, Duarte et al [81] also demonstrated intense TGF-β expression in bone samples with osteitis fibrosa from patients with ROD, which is accompanied by extremely high bone turnover. A study conducted by Santos et al [82] indicated that TGF-β expression in bone changes before and after parathyroidectomy. Because TGF-β modulates the functions of both osteoblasts and osteoclasts, these results are rational.…”
Section: Possible Role Of Tgf-β In Chronic Kidney Disease-mineral mentioning
confidence: 99%
“…They also presented that activation of Runx2 or TCF-4 coenhances TCF and Runx2 activity and increases TGF-β receptor I expression [86]. As described above, high TGF-β protein expression has been observed in high-turnover bones from patients with end-stage renal disease [81,82]. Existence of a positive regulatory loop between TGF-β and Wnt signaling may lead to the pathogenesis of high-turnover bone disease in CKD.…”
Section: Possible Role Of Tgf-β In Chronic Kidney Disease-mineral mentioning
confidence: 99%